Unraveling regulation of the small heat shock proteins by the heat shock factor HvHsfB2c in barley: Its implications in drought stress response and seed development - Reddy, Palakolanu Sudhakar; Kavi Kishor, Polavarapu B.; Seiler, Christiane; Kuhlmann, Markus; Eschen-Lippold, Lennart; Lee, Justin; Reddy, Malireddy K.; Sreenivasulu, Nese (Public Library of Science, 2014)
The rapid increase in heat shock proteins upon exposure to damaging stresses and during plant development related to desiccation events reveal their dual importance in plant development and stress tolerance. Genome-wide sequence survey identified 20 non-redundant small heat shock proteins (sHsp) and 22 heat shock factor (Hsf) genes in barley. While all three major classes (A, B, C) of Hsfs are localized in nucleus, the 20 sHsp gene family members are localized in different cell organelles like cytoplasm, mitochondria, plastid and peroxisomes. Hsf and sHsp members are differentially regulated during drought and at different seed developmental stages suggesting the importance of chaperone role under drought as well as seed development. In silico cis-regulatory motif analysis of Hsf promoters showed an enrichment with abscisic acid responsive cis-elements (ABRE), implying regulatory role of ABA in mediating transcriptional response of HvsHsf genes. Gene regulatory network analysis identified HvHsfB2c as potential central regulator of the seed-specific expression of several HvsHsps including 17.5CI sHsp. These results indicate that HvHsfB2c is co-expressed in the central hub of small Hsps and therefore it may be regulating the expression of several HvsHsp subclasses HvHsp16.88-CI, HvHsp17.5-CI and HvHsp17.7-CI. The in vivo relevance of binding specificity of HvHsfB2C transcription factor to HSE-element present in the promoter of HvSHP17.5-CI under heat stress exposure is confirmed by gel shift and LUC-reporter assays. Further, we isolated 477 bp cDNA from barley encoding a 17.5 sHsp polypeptide, which was predominantly upregulated under drought stress treatments and also preferentially expressed in developing seeds. Recombinant HvsHsp17.5-CI protein was expressed in E. coli and purified to homogeneity, which displayed in vitro chaperone activity. The predicted structural model of HvsHsp-17.5-CI protein suggests that the α-crystallin domain is evolutionarily highly conserved.